Apelin in Normal Pregnancy and Pregnancies Complicated by Placental Insufficiency. (August 2016) - Van Mieghem, Tim; Doherty, Anne; Baczyk, Dora; Drewlo, Sascha; Baud, David; Carvalho, Jose; Kingdom, John
Introduction: Apelin is a potent inotropic agent and causes endothelium-mediated vasodilation. Its cardiovascular profile suggests a role in the regulation of gestational hemodynamics. Methods: We longitudinally assessed maternal serum apelin levels and hemodynamics (cardiac output and total peripheral resistance) between 20 and 34 weeks gestation in 18 women at high risk of placental dysfunction. Placental apelin staining was assessed by immunohistochemistry in placentas from uncomplicated pregnancies (n = 6), preterm deliveries (n = 6), preeclampsia (PET, n = 8), and isolated intrauterine growth restriction (IUGR, n = 8). Placental apelin gene expression was assessed by quantitative polymerase chain reaction. Results: In the high-risk cohort, 4 fetuses developed isolated IUGR and 6 women developed PET. We obtained a median of 5 (range 2-9) hemodynamic and apelin measurements per woman. Apelin levels throughout gestation were best fitted by a quadratic curve. Apelin levels between 20 and 26 weeks gestation correlated with total peripheral resistance ( r = .57, P = .01) and showed a trend toward an inverse correlation with stroke volume ( r = −.42, P = .08). Apelin serum levels were 30% lower in pregnancies complicated by IUGR than in uncomplicated pregnancies or in women with preeclampsia ( P = .009). Placental apelin gene expression was similar in IUGR, PET, preterm, and term normal placentas. Apelin staining was seen both in syncytiotrophoblast and stroma of the placental villi. In IUGR placentas, apelin staining was strongly decreased in both compartments compared to normals. Preeclamptic placentas showed an intermediate staining. Conclusions: Apelin levels mirror the cardiovascular changes seen in pregnancy. Serum and placental apelin levels are decreased in IUGR.